Mobile Technology as an Alternative Teaching Strategy Amidst COVID-19 Hiatus: Exploring Pedagogical Possibilities and Implications for Teacher Development - Ali Gohar Qazi; Muhammad Yasir Mustafa; Fredrick Japhet Mtenzi; Martin Valcke (MDPI AG, 2023)
Amidst the COVID-19 pandemic, the education sector worldwide had to adapt rapidly from in-person to virtual modes of teaching and learning to mitigate the spread of the virus. In a short period of time, teachers were forced to find new and innovative ways of delivering education to their students to ensure the continuation of education. In this context, this paper investigates how teachers in Pakistan leveraged mobile technology as an alternative teaching strategy to provide access to and to ensure the continuation of education. Through in-depth interviews with 13 selected teachers, this study explores the potential of mobile technology to offer alternative teaching and learning arenas. The findings underscore the importance of embracing new pedagogical possibilities offered by mobile technology and the significance of effective teacher professional development in the post-pandemic era. This study provides valuable insights into the utilization of mobile technology in the education sector, even in the most challenging circumstances, and highlights the potential for mobile learning to contribute to education reform.